Corporate ESG Information Disclosures - E. V. Morozova (Учёт. Анализ. Аудит, 2024)
the purpose of the study was to assess the compliance of modern ESG reporting with the expectations formulated in the UN Global Compact (UNGC) report “Who Cares Wins”, and its subject is corporate ESG information as an element of improving the functioning of financial markets and society as a whole. The work used such general scientific research methods as analysis, abstraction, generalization, induction, and analogy. The author shows that despite the quantitative growth of ESG reports and the development of guidelines for the disclosure of ESG information, there are still difficulties and challenges in measuring the effectiveness of E&S activities and corporate ESG sustainability, and the interest in establishing and defining the connection between ESG and financial indicators continues; the concept of materiality in ESG reporting is characterized by a different and uneven ranking of priorities of ESG activities, as well as the distinction between financially material and financially non-material sustainability issues; currently, increasing the disclosure of corporate ESG information does not improve public confidence in sustainability efforts and results. In the course of the work, a review of publications on the measurement and disclosure of corporate ESG indicators was carried out. the conclusions drawn indicate that modern ESG reporting has partially overcome the shortcomings formulated in the UN Global Compact “Who Cares Wins”. Progress has been made in standardizing, measuring, disclosing, and publishing ESG information, but it is still considered to lack consistency and reliability. Moreover, it does not make a convincing case for its impact on company value. the results of the study — an analysis of the concept of strengthening the sustainability of financial markets and the role of ESG reporting — can be useful in theoretical research in the field of non-financial reporting.